1976
DOI: 10.1126/science.948744
|View full text |Cite
|
Sign up to set email alerts
|

[ 3 H]Morphine Localization in Myenteric Plexus

Abstract: Preferential binding of 3H-labeled morphine to satellite cells, but not to large neurons in the myenteric plexus, is demonstrated autoradiographically. Microfluorometric spectra of the plexus show nerve fibers that contain norepinephrine and impinge on satellite cells. Cells containing serotonin occur occasionally on longitudinal muscle outside the myenteric plexus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

1977
1977
1988
1988

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
(1 reference statement)
0
4
1
Order By: Relevance
“…Our supposition that the morphine-sensitive cells are the cholinergic efferents to the muscle is at variance with the interpretation by Diab, Dinerstein, Watanabe & Roth (1976) of their autoradiographic experiments. They found the PHI-morphine bound to a population of small cells in the myenteric plexus.…”
Section: The Site Ofaction Ofmorphinecontrasting
confidence: 65%
See 1 more Smart Citation
“…Our supposition that the morphine-sensitive cells are the cholinergic efferents to the muscle is at variance with the interpretation by Diab, Dinerstein, Watanabe & Roth (1976) of their autoradiographic experiments. They found the PHI-morphine bound to a population of small cells in the myenteric plexus.…”
Section: The Site Ofaction Ofmorphinecontrasting
confidence: 65%
“…They found the PHI-morphine bound to a population of small cells in the myenteric plexus. Diab et al (1976) referred to these cells as satellite cells but presented no ultrastructural evidence for such an identification. There are two reasons why the cells which they found to bind P3HI-morphine might be neurones rather than glial cells.…”
Section: The Site Ofaction Ofmorphinementioning
confidence: 99%
“…but had no lasting effect on the fast or slow e.p.s.p.s. The previous suggestion by Hirst & Silinsky (1975) that dopamine and noradrenaline may be equally likely candidates appears untenable in the light of more recent studies which have shown a virtual absence of dopamine within intestinal nerves (Diab, Dinerstein, Watanabe & Roth, 1976;Furness & Costa, 1980, 1982.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, the presence of opiate receptors has been demonstrated in the myenteric plexus of guinea-pig ileum (Diab et al 1976).…”
Section: Introductionmentioning
confidence: 99%
“…Endogenous opioids are known to be produced and secreted by several tissues of the body such as the small intestine (Goldstein 1973;Smith et al 1976;Polak et al 1977), adrenal medulla (Viveros et al 1979) and pituitary gland (Mains et al 1977;Roberts & Herbert 1977;Khalid et al 1982). Furthermore, the presence of opiate receptors has been demonstrated in the myenteric plexus of guinea-pig ileum (Diab et al 1976).…”
Section: Introductionmentioning
confidence: 99%